Users' Satisfaction as a Valid Measure for Information Resources: A Case of Public Libraries. Issue 3 (3rd April 2018) - Bashir, Faiza; Soroya, Saira Hanif; Khanum, Almas
ABSTRACT: The mission of public libraries is to serve the unique needs of their local communities. Public library User's play a very vital role in the development of these libraries by suggesting or recommending additions to the collection. This study aims to evaluate the satisfaction of users with the quality and quantity of library collection. A self structured questionnaire based on open and close ended question was constructed. A purposive sample of one hundred users was selected. The data were qualitatively analyzed using a thematic approach. Positive opinion observed related to the library response towards the suggested titles. Almost half the population of respondents was satisfied with the availability of their suggested titles in library. Most of them were dissatisfied regarding the maintenance of equal collection of books and they are not encouraged by the library staff during the books suggestion process. It concludes that there is a need to evaluate the existing library collections.